Efforts To Increase Agricultural Productivity and Marketing Through The Use Of Environmentally Friendly Products and Packaging Labelling in Pliken Village - Fathurrohman, Yusuf Enril; Watemin, Watemin; Kharismasyah, Alfato Yusnar; Rahma, Shalu Desta Arina; Alkhamdi, Aden Nuzuli Gita (Institute Of Advanced Knowledge and Science, 2025)
Pliken Village is one of the villages in Kembaran Sub-district, Banyumas Regency, which is rich in agricultural potential. The majority of the community work as farmers, but many also work as soybean tempe artisans. Farmers have not realized the importance of environmentally friendly products in agricultural production due to a lack of knowledge of the good and sustainable impacts of environmentally friendly products. In addition, the large number of tempe craftsmen makes Pliken Village the center of soybean tempe production. The high potential of soybean tempe production must be balanced with the widespread marketing of Pliken Village soybean tempe products. One strategy in marketing is seen from product packaging. There is no product labeling on soybean tempe products in Pliken Village. Product labeling will make Pliken Village's tempe soybean famous. In an effort to make farmers aware of the good impact of environmentally friendly products and the importance of product labeling on soybean tempe, it is necessary to empower agricultural productivity by using environmentally friendly products and marketing strategies through labeling. The solution offered is to provide information related to the concept of environmentally friendly products and training in making environmentally friendly products, as well as the concept of marketing strategies with product labeling. The targets of this service are active farmer groups and soybean tempe craftsmen. The methods used are lectures/counseling, mentoring, and direct practice of making environmentally friendly products. Activities began with an environmentally friendly product workshop, then socialization of marketing strategies through product labeling.